Quadrilátero ferrífero MG: fatores condicionantes do relevo - Daniel Peifer Bezerra (2014)
The Quadrilátero Ferrífero (QF) is one of the most important mineral provinces in the world, with a significant history of production of gold, iron and aluminum. Despite the geological knowledge about the QF be very expressive, the geology and geomorphology of QF are a 'puzzle' whose complexity is so great that the studies on its morphological evolution have not reached a consensus yet. The most commonly accepted hypothesis to explain the geomorphology of the QF, states that the spatial distribution of rocks with different resistance to denudation led to an inverted relief, where anticlines have been eroded and occupy the lower portions of the relief, while synclines remain suspended. Flanks of synclines would be protected by resistant lithologys (quartzites and itabirites) and these remain suspended constituting highlands because of the great strength of these rock types. However, many studies have found evidence of recent tectonic activity in small sedimentary deposits. In this sense, this dissertation sought to test the geomorphological constraints of the relief of the QF, trying to differentiate the importance of the characteristics of bedrock and diastrophism in the geomorphological evolution of the QF. For this, the assessment of the statistical and graphical relations between the lithological distribution, altimetric distribution and the distribution of Stream-Length (SL) index for the QF was performed. The assumption made for the use of this method is that if the differential erosion is the main relief control, it must be find a positive relationship between altimetric distribution, lithological distribution and spatial distribution of SL index values. The relief control by active tectonic demand, in turn, a misfit between relief and the passive controls of the same. The results show that: does not occur lithological control in the altimetric distribution; does not occur lithological control on the distribution of values of SL index; the assumption of correlation between the "Highlands" of the QF and resistant rocks (quartzite and itabirites) is not correct. In addition, altimetry and SL index are distributed unevenly in QF: the basin of the Upper Rio Conceição exhibits greater stream power and greater altimetry than the basin of the Upper Rio das Velhas. Therefore, the explanation model of the QF relief by differential erosion was refuted. From the interpretation of the results was proposed that the eastern portion of the QF was possibly uplifted from different fronts that represent ancient structures, with Brasiliana age (650-500 Ma) and vergence W, that were reactivated with different intensities during the Cenozoic. This reactivations were possibly responsible for the inferred tilting of the basins of QF and the areas of high SL concentrated in the Upper Rio Conceição basin / east boundary of the Upper Rio das Velhas basin.